Photopolymerized hybrids containing TiO2 nanoparticles for gradient-index lens - Messaddeq, Sandra Helena; Bonnet, Anne-Sophie; Santagnelli, Silvia Helena [UNESP]; Salek, Guillaume; Colmenares, Yormary N.; Messaddeq, Younès [UNESP] (Elsevier, 2019)
An ultra violet (UV)-cured nanocomposite material, based on TiO2 nanoparticles was prepared by sol-gel process from 3-(methacryloxy)propyltrimethoxysilane (MPTS) and 1,12-dodecanediol dimethacrylate (DDDMA). The evolution of structural properties for the inorganic-organic hybrid network was studied by FT-IR and NMR during UV curing, while the photo-polymerization kinetics of hybrid organic-inorganic matrix was evaluated using Raman spectroscopy. It was found that the three-dimensional (3D) organic-inorganic network was formed mainly by polymerization of C=C bonds in methacrylate units and Si–O–Ti bonds were formed when the hybrid matrix solution was cured by UV light. The influence of TiO2 dosage on the particle size and morphology was investigated by DLS and TEM respectively. We observed that introducing TiO2 nanoparticles into the polymeric matrix allows to fabricate a bulk nanocomposite with good optical quality and with positively charged particles that enables us to tailor the refractive index of the material; a property that can be potentially used in the production of GRIN lenses.
Keywords: Hybrid organic-inorganic sol-gel; Polymerization degree; TiO2 nanoparticles; UV-Curing